Designing Bilingual and Culturally Inclusive Learning Materials: A Needs Analysis of Pop-Up Books in English Instruction - Rizky Amelia Putri; Sary Silvhiany; Machdalena Vianty (Universitas Pendidikan Mandalika, 2026)
Inclusive education for Deaf students in Indonesia continues to face pedagogical challenges, particularly in English language instruction due to the limited availability of accessible and appropriate learning materials. Deaf learners often experience difficulties in vocabulary acquisition and comprehension when instruction relies heavily on text-based approaches. This study aims to conduct a needs analysis to inform the development of culturally inclusive and bilingual English learning materials for Deaf students. Using a qualitative research design, structured interviews were conducted with two English teachers and eight Deaf students at SLBB YPAC Palembang. The data were analyzed using Target Situation Analysis (TSA) and Present Situation Analysis (PSA) frameworks. The findings reveal that Deaf students require strong visual support and the integration of Indonesian Sign Language (BISINDO) to facilitate vocabulary learning and comprehension. Participants also emphasized the importance of incorporating local cultural elements from Palembang, such as traditional food, arts, and dance, to enhance engagement and strengthen cultural identity. Pop-up books emerged as effective multimodal learning media due to their visual, tactile, and interactive features that align with Deaf students’ learning preferences. In conclusion, this study highlights the urgent need for bilingual, multimodal, and culturally responsive English learning materials. The findings provide practical implications for the development of inclusive instructional resources that can reduce learning barriers and promote equitable English language education for Deaf learners.